THE INFLUENCE OF CREATIVE READING TEACHING MATERIALS BASED ON RIAU MALAY IN HIGHER EDUCATION - Kurniaman, Otang; Permana, Dede; Rahman, Fadhila; Syafitra, Viony; Radini, Radini; Andesta Putra, Rezi (PD PGMI se Indonesia, 2024)
Implementation of teaching materials based on Riau Malay culture is used to determine the effect on students' creative reading skills. The importance of teaching materials for lecturers to facilitate the delivery of material in lectures. This study uses a quasi-experimental method with a one group pretest-posttest design with a sample of 40 PGSD students. The results of the study to measure the effect must follow several stages, namely the normality test produced that the value of 0.002 <0.05 is not normally distributed. Homogeneity test 0.371> 0.05 then the results of the hypothesis are homogeneously distributed. Because of the two tests with different results, the data is not normal and homogeneous so that parametric testing is needed to find the effect of creative reading teaching materials based on Riau Malay culture by conducting the Wilcoxon test. Then the effect test was carried out 0.011 <0.05, it was concluded that the use of creative reading teaching materials based on Riau Malay culture had an effect on students' creative reading skills.